Correlation Between Parental Knowledge of Oral Health and Dental Caries Incidence Among Preschool Children at Ar-Rahman Foundation Jombang - Heva Pratiwi; Silvia Prasetyowati; Sunomo Hadi; Imam Sarwo Edi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental caries remains one of the most prevalent oral health problems among preschool children, and inadequate parental knowledge is often identified as a major contributing factor. Despite existing preventive programs, many parents still lack sufficient understanding of proper oral hygiene practices, which may exacerbate caries risk during early childhood. This study aimed to analyze the relationship between parental knowledge of oral health and the incidence of dental caries among preschool children enrolled at PAUD and Kindergarten under the Ar-Rahman Foundation in Jombang. A quantitative, cross-sectional design was employed involving 39 parents selected through total sampling. Parental knowledge was assessed using a structured questionnaire, while children’s dental caries status was measured using the deft index following WHO guidelines. Data were analyzed using the Chi-square test with a significance level of α = 0.05. The results showed that more than half of the parents (51.3%) possessed low knowledge regarding oral health, while the prevalence of dental caries among preschool children remained high. Although descriptive patterns suggested that children of parents with lower knowledge tended to exhibit higher deft scores, statistical results (p = 0.286) indicated no significant association between parental knowledge and dental caries incidence. These findings highlight that knowledge alone may not sufficiently influence caries outcomes without being accompanied by consistent practice, behavioral reinforcement, and adequate access to oral health services. In conclusion, the high prevalence of dental caries observed in this study underscores the need for improved parental education and comprehensive health promotion strategies. Strengthening school-based oral health programs and enhancing parental involvement in preventive practices are essential to reducing the burden of caries among preschool-aged children.